2015
DOI: 10.1088/1742-5468/2015/08/p08018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diffusion in simple discontinuous absorbing transition models

Abstract: Discontinuous transitions into absorbing states require an effective mechanism that prevents the stabilization of low density states. They can be found in different systems, such as lattice models or stochastic differential equations (e.g. Langevin equations). Recent results for the latter approach have shown that the inclusion of limited diffusion suppresses discontinuous transitions, whereas they are maintained for larger diffusion strengths. Here we give a further step by addressing the effect of diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
2
8
2
Order By: Relevance
“…Results showed that limited competition rates are sufficient for the suppression of phase coexistence. This is in partial contrast with previous results [18,20] like particle diffusion and distinct annihilation rules do not shift the discontinuous transitions. As a final comment, we mention that all results for the first-order transitions reinforce previous claims over a common finite-size scaling for nonequilibrium transitions [18,20,21], in which in similarity with the equilibrium case, relevant quantities scale with the system volume.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Results showed that limited competition rates are sufficient for the suppression of phase coexistence. This is in partial contrast with previous results [18,20] like particle diffusion and distinct annihilation rules do not shift the discontinuous transitions. As a final comment, we mention that all results for the first-order transitions reinforce previous claims over a common finite-size scaling for nonequilibrium transitions [18,20,21], in which in similarity with the equilibrium case, relevant quantities scale with the system volume.…”
Section: Discussioncontrasting
confidence: 99%
“…For equilibrium systems, the maximum of χ and other quantities scale with the system volume and its position α L obeys the asymptotic relation α L = α 0 − c/L 2 [24,25], being α 0 the transition point in the thermodynamic limit and c a constant. Recent papers [18,26,20,21] have shown that similar scaling is verified for nonequilibrium phase transitions. Alternatively, the transition point can also be estimated as the value of α L in which the two peaks of the probability distribution have equal weights (area) [26,21].…”
Section: Numerical Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…To obtain stronger evidence for our view mentioned in this work and deeper insight into the phenomena, further experiments, such as exploring direct visualization of the vortex configuration [52,59], as well as theoretical investigation, may be needed. We believe that the present study will stimulate similar experiments and analysis in other systems where the dynamic ordering and disordering would be observed [10,16,41,48,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Resultssupporting
confidence: 55%